Two species of the deep-water shrimp genus Nematocarcinus A. Milne–Edwards, 1881 (Crustacea, Decapoda, Caridea, Nematocarcinidae) from the Mexican Pacific - Hernandez-Payan, J.c.; Hendrickx, M.e. (Zootaxa, 2016)
The distribution of two species of the deep-water shrimp genus Nematocarcinus A. Milne-Edwards, 1881, occurring off the west coast of Mexico is analyzed based on a large series of recently collected material. Nematocarcinus faxoni Burukovsky, 2000, is by far the most common and abundant species in the area and it is distributed throughout the central and southern Gulf of California and off the entire Baja California Peninsula south to 17º10’15”N. Based on characteristics observed in the new samples and in the type material, N. agassizii Faxon, 1893, is reinstalled as a valid species, and no longer considered a junior of N. gracilipes A. Milne-Edwards, 1881, as proposed by Cardoso & Burukovsky (2014). Along the Pacific coast of Mexico, N. agassizii exhibits a more restricted distribution and it was collected only off the Baja California Peninsula. Previous records of this species in the Gulf of California, where N. faxoni was the only representative of the genus captured during this survey, are considered doubtful.